The Performance of the Maluku Provincial General Election Commission in the 2024 Presidential and Vice Presidential Election in Ambon City - Rangkoly, Matheus; Zainal Abidin Rengifurwarin; Iriane Sosiawaty Ponto (Journal of International Multidisciplinary Research, 2025)
This study aims to analyze and describe the performance of the General Election Commission (KPU) of Maluku Province in organizing the 2024 Presidential Election, and the influencing factors in Ambon City. The research problems addressed in this study are: 1) How is the performance of the KPU of Maluku Province in organizing the 2024 Presidential Election? and 2) What are the supporting and inhibiting factors in Ambon City? The study involved 14 informants. The research method used is a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. Data were analyzed using descriptive qualitative analysis techniques. The findings show that the performance of the KPU of Maluku Province in organizing the 2024 Presidential Election in Ambon City is in good condition, based on dimensions such as work responsiveness, work accountability, work effectiveness, and work efficiency. This performance is influenced by factors such as human resources (HR), technological support, collaboration with stakeholders, and community participation.